Здание мечети пророка Муххамеда в Измаиле: новые факты и интерпретации - Сапожников, И.В. (Материалы по археологии Северного Причерноморья, 2009)
This article is devoted to the monument of the end of X VI century — unique for the entire North-Western Black Sea — building a mosque prophet Muhhameda located on the bank of the Danube, on the territory of former Izmail fortress. Based on the analysis of written sources, topographical plans and iconographic materials the author reconstructed main stages in the history of this building, which in XIX - the first half of the XX centuries used as a Christian church. It also sets out the summary results of archaeological excavations of Izmail expedition in 2007, which discovered rests of the foundation of the minaret, as well as traces of more recent modifications of this temple for the needs of Orthodox church.